Promoting perceived creativity and innovative behavior: Benefits of future problem-solving programs for higher education students. (March 2023) - Alt, Dorit; Kapshuk, Yoav; Dekel, Heli
Highlights: A future problem-solving program was employed in two higher education settings. Students' perceived awareness of future problem-solving, creativity, and innovative behavior were assessed. Data were collected from 432 undergraduate students. FPS programs increased the participants' awareness of future problems, perceived creativity, and innovative behavior. Abstract: While it is widely acknowledged that Future Problem Solving (FPS) programs may have the potential for engendering creativity and innovation skills in pupils, a somewhat opaque landscape emerges in terms of identifying the benefits of such programs for higher education students. In this quasi-experimental study, an FPS program was employed in two study tracks: peace education and teacher training. Its main objective was to assess students' perceived awareness of future problem-solving, creativity, and innovative behavior before and after the program implementation. Another aim was to evaluate the potential links between the three variables. Data were collected from 432 students by using three measurements: Awareness of future problems scale ; Short Scale of Creative Self - SSCS ; and Innovative Behavior scale. Findings showed that the participants' awareness of future problems, their belief in their ability to produce creative ideas, and their perceived innovative behavior have increased by the end of the FPS program implementation, relative to its onset. Non-significant findings were detected in the control group. The empirical model indicated the mediating role of perceived creativity in linking awareness of future problems to students' perceived innovative behavior.